Attainment of target rifampicin concentrations in cerebrospinal fluid during treatment of tuberculous meningitis. (July 2019) - Mezochow, Alyssa; Thakur, Kiran T.; Zentner, Isaac; Subbian, Selvakumar; Kagan, Leonid; Vinnard, Christopher
Highlights: This study evaluated rifampicin pharmacodynamic target attainment in tuberculous meningitis. Under standard dosing, a rifampicin minimum inhibitory concentration (MIC) of 0.5 mg/l was a nearly unattainable target. Intensified rifampicin dosing is supported by pharmacokinetic modeling/simulation. Abstract: Objective: There is considerable uncertainty regarding the optimal use of rifampicin for the treatment of tuberculous (TB) meningitis. A pharmacokinetic modeling and simulation study of rifampicin concentrations in cerebrospinal fluid (CSF) during TB meningitis treatment was performed in this study. Methods: Parameters for rifampicin pharmacokinetics in CSF were estimated using individual-level rifampicin pharmacokinetic data, and the model was externally validated in three separate patient cohorts. Monte Carlo simulations of rifampicin serum and CSF concentrations were performed. The area under the rifampicin CSF concentration-versus-time curve during 24 h (AUC0–24 ) relative to the minimum inhibitory concentration (MIC) served as the pharmacodynamic target. Results: Across all simulated patients on the first treatment day, 85% attained the target AUC0–24 /MIC ratio of 30 under a weight-based dosing scheme approximating 10 mg/kg. At the rifampicin MIC of 0.5 mg/l, the probability of AUC0–24 /MIC target attainment was 26%. With an intensified dosing strategy corresponding to 20 mg/kg, target attainment increased to 99%, including 93% with a MIC of 0.5 mg/l. Conclusions: Under standard dosing guidelines, few TB meningitis patients would be expected to attain therapeutic rifampicin exposures in CSF when the MIC is ≥0.5 mg/l. Either downward adjustment of the rifampicin MIC breakpoint in the context of TB meningitis, or intensified rifampicin dosing upwards of 20 mg/kg/day, would reflect the likelihood of pharmacodynamic target attainment in CSF.